HIV-1 nonsubtype B distribution across certain resource-rich countries. Issue 5 (September 2009) - Brindicci, Gaetano; Tartaglia, Alessandra; Saracino, Annalisa; Monno, Laura; Angarano, Gioacchino
The distribution of different HIV subtypes follows a geographical trend. HIV-1 (the most widespread type of HIV worldwide) is classified into three genetic groups: major (M), outlier (O) and novel (N). HIV-1 group M viruses have been classified into nine subtypes. Analysis of full-length genome sequencing has revealed intersubtype recombinants, which are thought to originate from individuals simultaneously infected with viruses of two or more subtypes. The extensive genetic variability of HIV-1 and international travel are important factors in its spread worldwide. The aim of this review is to describe the changing patterns of nonsubtype B prevalence in resource-rich countries and verify how these subtypes influence transmission, disease progression, mutational patterns of resistance, as well as response to therapy.